2020
DOI: 10.25299/sportarea.2020.vol5(1).4621
|View full text |Cite
|
Sign up to set email alerts
|

Profil Psikologis Atlet Pekan Olahraga Nasional (PON) Papua Menuju PON XX Tahun 2020

Abstract: This study aimed to identify the psychological profile of athletes PON Papua. In addition, each psychological aspect of Athlete PON Papua will be analyzed the condition of each psychological aspect along with the spread of athletes and their presentation. The method used in this study is a survey method with expost facto research design. The population in this study are athletes Papua who will be prepared road to PON XX 2020. The sampling technique used purposive sampling with the criteria for athletes PON Pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 6 publications
0
9
0
18
Order By: Relevance
“…Other studies that have been conducted have also shown that elite athletes in team sports have high psychological characteristics (Nopiyanto, Dimyati, & Dongoran, 2019). Likewise, athletes at the national level have high psychological characteristics (Dongoran & Kalalo, 2020).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies that have been conducted have also shown that elite athletes in team sports have high psychological characteristics (Nopiyanto, Dimyati, & Dongoran, 2019). Likewise, athletes at the national level have high psychological characteristics (Dongoran & Kalalo, 2020).…”
Section: Resultsmentioning
confidence: 89%
“…Other studies also state that there are no differences in the psychological characteristics of male and female athletes in terms of gender in the martial arts and fighting sports. (Dongoran & Kalalo, 2020). Furthermore, it is known that there is no difference between the motivational aspects of pencak silat and boxing athletes (Dongoran, Nopiyanto, Saputro, & Nugroho, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Pembinaan yang dilakukan akan sesuai dengan harapan apabila dilaksanakan secara efisien, sitematik, dan berkelanjutan, karena suatu proses pembinaan olahraga membutuhkan waktu yang lama (Nugraha & Pratama, 2019). Faktor pembinaan yang diberikan melalui program manajemen dan pembinaan yang terstruktur dan berkelanjutan dengan konsep yang baik akan menjadi tujuan prestasi pada ajang cabang tertentu sebagai penjaringan bagi atlet berprestasi dalam meningkatkan harkat dan martabat sebagai individu maupaun negara di iven Internasional (Dongoran, Kalalo, & Syamsudin, 2020).…”
Section: Pendahuluanunclassified
“…In addition, there were also articles that examined Papuan PON athletes, but it was not the construct of anxiety that was discussed, but the psychological aspect of the athletes, namely the psychological profile. (Dongoran, Kalalo, & Syamsudin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous studies conducted on PON athletes (Maulana & Khairani, 2017;Ikhsan, Razali, & Rinaldy, 2016;Dongoran, Kalalo, & Syamsudin, 2020) and there are inconsistent findings even though the constructs studied are the same (Sukadiyanto, 2006) the researchers consider that it is important to conduct research on anxiety in Papuan elite athletes who are projected to compete in the XX PON by involving several sports and considering the athletes' gender variable. Therefore, this study aims to uncover and to compare the anxiety of elite Papuan athletes based on the type of sport and gender.…”
Section: Introductionmentioning
confidence: 99%